2012
DOI: 10.1515/bot-2012-0501
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria and macroalgae from an arid environment mangrove on the east coast of the Baja California Peninsula

Abstract: We describe the assemblage of cyanobacteria and macroalgae on Avicennia germinans pneumatophores, Rhizophora mangle aerial roots, and within the tidal channel of a mangrove located in a lagoon bordering the east coast of the Baja California Peninsula, from samples collected every 2 months from May 2005 to May 2006. A total of 68 species were found: 21 cyanobacteria, 1 Xanthophyta, 25 Chlorophyta, 1 Ochrophyta-Phaeophyceae, 19 Rhodophyta, and 1 Anthophyta. Species richness varied between habitats; pneumatophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In a mangrove from Baja California, Mexico, 21 cyanobacterial species, including Heteroleibleinia sp. and Johannesbaptistia sp., have been found either growing on Avicennia germinans pneumatophores and Rhizophora mangle aerial roots or on epiphytic algae (Pérez-Estrada et al 2012). Potts (1979) detected cyanobacterial growth zonation in Avicennia marina pneumatophores, with Scytonema sp.…”
Section: Epiphytic Mangrove Cyanobacteriamentioning
confidence: 99%
“…In a mangrove from Baja California, Mexico, 21 cyanobacterial species, including Heteroleibleinia sp. and Johannesbaptistia sp., have been found either growing on Avicennia germinans pneumatophores and Rhizophora mangle aerial roots or on epiphytic algae (Pérez-Estrada et al 2012). Potts (1979) detected cyanobacterial growth zonation in Avicennia marina pneumatophores, with Scytonema sp.…”
Section: Epiphytic Mangrove Cyanobacteriamentioning
confidence: 99%
“…Researchers have also found higher amounts of mangrove macroalgae during the summer season (Steinke & Naidoo 1990), which was found to be influenced by nutrient availability, temperature, and light intensity. In contrast, studies by Perez-Estrada et al (2012), Nedumaran and Perumal (2009), Liu et al (2001), El-Sharouny et al (2001), and Lin et al (1997 found that mangrove macroalgae grow throughout the year, and seasonal influences on their growth were not noticed. It has been observed that the three stations in the Sibuti mangroves have their own biotic and abiotic factors that influence the species abundance of macroalgae (Broderick & Dawes 1998).…”
Section: Discussionmentioning
confidence: 89%
“…1984 ; Hussain & Khoja 1993 ; Selvakumar & Sundararaman 2001 ; Nedumaran et al . 2008 ; Pérez-Estrada et al . 2012 ; Silambarasan et al .…”
Section: Discussionunclassified
“…nigroviride, Spirulina cf. labyrinthiformis, Spirulina meneghiniana), appear to be cosmopolitan in mangrove ecosystems (Dor et al 1984;Hussain & Khoja 1993;Selvakumar & Sundararaman 2001;Nedumaran et al 2008;Pérez-Estrada et al 2012;Silambarasan et al 2012;Sakthivel & Kathiresan 2013).…”
Section: Previous Records Of the Morphospecies Encounteredmentioning
confidence: 99%